Eficácia do chá verde (Camellia sinensis (L.) Kuntze) no tratamento da periodontite: Revisão sistemática e meta-análise - Melo, Jéssica Gomes Alcoforado de (2019)
This study had the goal to analyze the scientific evidence regarding the efficiency of green tea (Camellia sinensis) in its different forms and applications for the treatment of periodontitis. It was searched in the electronic databases PubMed/MEDLINE, Scopus, Web of Science, Cochrane, Scielo, Lilacs, Science Direct, in the gray literature, as well as manual search, until April 2019. Then, it was randomized clinical trials evaluating the green tea as an adjuvant therapeutic agent in the treatment of periodontitis. Two independent reviewers selected the studies, extracted the data and analyzed the risk of bias of the studies using the Cochrane RoB 2.0 instrument and the analysis of the quality of certainty using GRADE. Initially, 3,025 studies were found, of which nine were included in the qualitative and quantitative analysis. The risk of bias was low in only four studies, high in four, and only one of the nine studies was considered to have some problems. Four ways of presenting green tea were identified: sachets, hydroxypropylcellulose strips, gel and dentifrice. Green tea, in all studies, was given in combination with scraping and root straightening. The treatment time ranged from 21 days to 6 months. It was verified from the meta-analysis that the use of green tea, specifically as a sachet, significantly reduced probing bleeding (SMD = -0,71 [-1,39, -0,03] p = 0,04, I² = 82%) and the gingival index (SMD = -0,78 [- 1,33, -0,23] p = 0,006, I² = 80%). The presentation forms as sachet and dentifrice reduced plaque index (SMD = -0,63 [-1,18, -0,08] p = 0,02, I² = 77%). To reduce the probing depth, there was no significant difference between using green tea or just scraping and root straightening (SMD = -0,27 [-0,97, 0,42] p = 0,44, I² = 89%). The certainty of the evidence for the depth of probing was very low. The scientific evidence that suggest the efficiency of the usage of green tea adjunct to periodontal therapy is weak. Thus, it is necessary to perform additional studies with better methodological quality to confirm the evidence.